Unlocking 'fixed narratives' in the pursuit of social innovation - Hanna, Anne-Marie (Research of GSB, 2018)
We live in an age where our most significant 'story' is becoming that of a growing population living on a resource scarce planet. The need for us to do things differently is clear, increasing our awareness of the importance for social innovation around the world, yet the overriding narrative of our time remains embedded in a value system that maintains things just as they are. By looking at the stories we tell and the ways we tell them this study seeks to understand the role that 'narrative' plays in shaping our world, the power it has to influence an alternative reality, and its significance in creating conditions that are conducive for social innovation to occur. This paper gains a deeper understanding of the value systems in which our storytelling behaviour seems to be fundamentally entrenched by exploring the differences between how we understand and make sense of stories of commercial, as opposed to social, interest. In doing so, it has tried to gain insight into how we have successfully managed to sustain and fuel the growth of a global culture that rooted in an extrinsic value system, while we have failed to engender a sense of social responsibility, justice and equality. By conducting a series of participatory action research workshops across four different case study contexts, the research sought to challenge three core elements identified in the literature as occurring in narrative patterns: (1) narratives appear to be framed within either a negative or a positive framework; therefore, reflecting only a 'partial story', and perpetuating stereotypes or incomplete truths; (2) they are generally told by a single, external storyteller, with a very clear agenda; and (3) they are constructed to appeal to extrinsic values. The study set out to understand how we might unlock fixed narratives in the pursuit of social innovation - reconstructing new narratives that could in turn influence and perpetuate alternative realities. The workshop approach drew on influences from three practice-based methods: Theory U, human-centred design and elements of mindfulness practices. They were designed to prioritise story creation by multiple storytellers from inside the case study context, encourage the exploration of both negative and positive aspects of an experienced truth, and appeal to intrinsic values by creating the space for emergence and honesty. The workshops took place at a non-profit organisation, a private ii company, a public sector community health centre, and with an independent group of individuals from the same area. The core finding of this research was that by gaining a sense of 'agency' over their own capacity to identify, shape and share their own story, participants appeared able to identify and deconstruct 'fixed narratives' and move towards reconstructing a 'new, shared narrative' that was more inclusive of everyone's lived experience. A series of common factors appeared to play a consistently significant role in creating the conditions for this to take place. Some form of mindfulness, or body-based, practice was effective in encouraging participants to connect to 'experienced truths'. The use of different media to identify and create their stories increased participants' capacity to connect with their sense of control over shaping their own narrative, and the quality of listening within each group affected the quality of the story and the storyteller's own level of engagement. This appeared to lead to what is referred to in this paper as 'narrative agency'. The above factors also appeared to contribute to a common 'journey' or eight-stage experience. This consisted of fully entering the narrative workshop space (grounding), witnessing their authentic personal story (activating), articulating and sharing with a group honestly (connecting), embodying the emergent personal narrative (consolidating), gaining a sense of ownership and control over their own story (agency), integrating their own story with the experiences and stories of others allowing a new shared narrative to emerge (integrating), and demonstrating a desire to co-create a new narrative to inform new authentic actions (co-creating). This research demonstrated that it can be challenging to separate ourselves from the 'fixed stories' we have come to claim as our own and truly create the space and time to connect with our deepest needs, thoughts and desires. Consequently, we often have no real 'agency' over our stories. The study indicated that a deeper understanding of how to create conditions that generate a sense of 'narrative agency' could contribute to emerging practices in the field of social innovation, such as human-centred design and Theory U, and potentially inform new products, processes and systems.